The effect of environmental performance on the competitiveness in product market - Dudran, Amin Panahi; Moradi, Majid; Khoshkar, Farzin (Eximia, 2021)
The objective of this research is to investigate the effect of environmental performance on competitiveness in the product market. Noticeably, the research period of this research is 2012-2019. Moreover, the research has two hypotheses, and the methodology of research based on objective is applied and based on nature and content is correlational. The research was conducted in the framework of deductive-inductive reasoning and panel analysis was used to analyze the hypotheses. The results of hypothesis testing showed that environmental performance has a negative and significant effect on competitiveness in the product market (Herfindahl-Hirschman index). However, Performance has no significant effect on competitiveness in the product market (Lerner index).